Associação entre os níveis séricos do marcador de permeabilidade intestinal zonulina e alimentação - Assmann, Patrícia (My University, 2020)
Introduction: Zonulin is a protein that modulates the opening of narrow junctions in the small intestine, associated with increased intestinal permeability. Objective: To evaluate the association between food consumption and serum zonulin levels. Methods: Cross-sectional study, including 73 individuals. Zonulin concentrations were assessed by serum samples, using the ELISA kit. Food intake was assessed using a food frequency questionnaire validated for the population of southern Brazil. Comparison analyzes between groups with low and high zonulin, correlation analyzes and focused main component analysis were used to verify the association of dietary components and food groups with zonulin levels. Sensitivity analyzes were performed including only good rapporteurs, using Goldberg and Black index between 0.76 and 1.24. Results: The group with the lowest zonulin levels had the highest consumption of total fats (78.11±14.27 vs. 70.34±18.90 g/day; p=0.043), polyunsaturated fatty acids (20.91±7.21 vs. 17.51±7.15 g/day; p=0.047) and saturated [22.7(20.7 - 24.9) vs. 20.9(18.7-23.7); p=0.036], as well as among good rapporteurs (p<0.05).There was a negative correlation between zonulin levels and the glycemic index of the diet (-0.261;p=0.026) and (-0.340; p=0.043), polyunsaturated fatty acid (-0.241; p=0.040) and (-0.480; p=0.003) respectively in the total sample and among the good rapporteurs, Total Lipids (-0.341; p=0.042) among the good rapporteurs. In the main component analysis focused, there was an inverse relationship between polyunsaturated fatty acids and zonulin, in the group of good rapporteurs. Conclusion: The highest intake of polyinstaturated fatty acids is associated with lower levels of serum zonulin in humans. [resumo fornecido pelo autor]
Introdução: A zonulina é uma proteína que modula a abertura das junções estreitas no intestino delgado, associada a aumento da permeabilidade intestinal. Objetivo: Avaliar a associação entre consumo alimentar e níveis séricos de zonulina. Métodos: Estudo transversal, incluindo 73 indivíduos. As concentrações séricas de zonulina foram avaliadas por teste de ELISA. A ingestão alimentar foi avaliada por questionário de frequência alimentar validado para a população do sul do Brasil. Análises de comparação entre grupos com baixa e alta zonulina (de acordo com a mediana), análises de correlação e análise de componentes principal focada foram utilizadas para verificar a associação de componentes dietéticos com níveis de zonulina. Análises de sensibilidade foram realizadas incluindo apenas bons relatores, utilizando índice de Goldberg e Black entre 0,76 e 1,24. Resultados: O grupo de menores níveis de zonulina apresentou maior consumo de gorduras totais (78,11±14,27vs.70,34±18,90 g/dia; p=0,043), ácidos graxos poli-insaturados (20,91±7,21vs. 17,51±7,15 g/dia; p=0,047) e saturados [22,7 (20,7 ? 24,9) vs.20,9 (18,7- 23,7); p=0,036], assim como entre os bons relatores (p<0,05). Houve correlação negativa dos níveis de zonulina com índice glicêmico da dieta (-0,261; p=0,026) e (-0,340; p=0,043), ácido graxo poli-insaturado (-0,241; p=0,040) e (-0,480; p=0,003) respectivamente na amostra total e entre os bons relatores, Lipídeos Totais (-0,341; p=0,042) entre os bons relatores. Na análise de componentes principais focada, houve uma relação inversa entre ácidos graxos poli-insaturados e zonulina, no grupo de bons relatores. Conclusão: A maior ingestão de ácidos graxos poliinstaturados está associada a menores níveis de zonulina sérica em seres humanos. [resumo fornecido pelo autor]
Keywords: Nutrição; Intestinos - Aspectos nutricionais; Alimentos - Consumo; Microbioma gastrointestinal